2013
DOI: 10.1007/s00204-013-1159-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of cardiac hypertrophy by sunitinib in vivo and in vitro rat cardiomyocytes is influenced by the aryl hydrocarbon receptor signaling pathway

Abstract: Sunitinib (SUN) is a new tyrosine kinase inhibitor that possesses both anti-angiogenic and anti-tumor activities. Although SUN has improved survival rate in cancer patients, cardiotoxicity has been reported as a significant side effect. Several studies suggested a role for the aryl hydrocarbon receptor (AhR) and its regulated genes such as cytochrome P4501A1 (CYP1A1) in the pathogenesis of heart failure and cardiac hypertrophy. To test the hypothesis that SUN induces cardiac hypertrophy through the modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 59 publications
5
37
0
Order By: Relevance
“…In this context, we have recently shown that development of cardiac hypertrophy by SUN in vivo and in vitro rat cardiomyocytes is influenced by the aryl hydrocarbon receptor signaling pathway [33]. In addition, previous mechanistic studies have reported that SUN elicits harmful cardiac effects through inhibiting AMPK and RSK and damaging the mitochondrial [34] and increased autophagic flux [35].…”
Section: Discussionmentioning
confidence: 93%
“…In this context, we have recently shown that development of cardiac hypertrophy by SUN in vivo and in vitro rat cardiomyocytes is influenced by the aryl hydrocarbon receptor signaling pathway [33]. In addition, previous mechanistic studies have reported that SUN elicits harmful cardiac effects through inhibiting AMPK and RSK and damaging the mitochondrial [34] and increased autophagic flux [35].…”
Section: Discussionmentioning
confidence: 93%
“…Callero et al reported that activating AHR with an agonist inhibited cell growth in a dose-dependent manner in RCC cell lines (24 ). It was also found that sunitinib, a tyrosine kinase inhibitor used for metastatic ccRCC, induced CYP1A1 expression through AHR in breast cancer (25 ). Aminoflavone, which has an antiproliferative effect on human breast cancer cells mediated by AHR, is also applied in clinical trials as a new anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…The protection against cisplatin and arsenic trioxide-induced cardiotoxicity has been attributed to the increase in the endogenous anti-oxidant enzymes activity namely, SOD, catalase, and glutathione peroxidase [270,277], in addition to activation of the anti-oxidant NRF2-heme oxygenase-1 pathway [276], suggesting the importance of the anti-oxidant properties of resveratrol in these models as well. Recently, an in vitro study has reported that resveratrol protects against sunitinib-induced hypertrophy in H9c2 cells [278]. The authors of that study proposed that resveratrol prevents hypertrophy by antagonizing the aryl hydrocarbon receptor (AhR) and inhibiting CYP1A1 enzyme [278], suggesting that resveratrol may also protect against chemotherapy-induced cardiomyopathy through its AhR-antagonistic properties.…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%